Strategic Planning Aktivitas Wisata Alam di Panorama Tabek Patah Kecamatan Salimpaung Kabupaten Tanah Datar - Ariza, Tesa Fitri; Kasmita, Kasmita; Suyuthie, Hijriyantomi (Journal of Home Economics and Tourism, 2017)
This research aims to determine the internal factors and external factors of the Panorama Tabek Patah and then devise the strategic planning activities of nature tourism in Panorama Tabek Patah. This research is descriptive research with qualitative and quantitative data. The technique of data collection is done using the method of observation, interview, questionnaire and documentation The sample of this research are some of the informants consisting of the Department of culture Tourism Youth and Sports (3 people), the Manager of Panorama Tabek Patah (1 person) community around tourist attraction (3 people), as well as visitor at the attractions (65 people) by using purposive sampling technique. The data obtained were analyzed by reduction of the data, the presentation of data, conclusions and taking a level percentage of achievement of the respondentsStrategic planning for nature tourism activities that will be developed are: 1. Making a spot at the place to enjoy the sights, promoting sightseeing activities as one of the competitive activities and prepare a tourguide that can guide tourists in conducting activities sightseeing. 2). Making tracks for hiking, training the community on a regular basis, utilizing the community or youth nagari to maintain the security of hiking activities, create routes and codes regarding hiking. 3. Reviving the activities of the flying fox, making a collaboration with tourism and the local government. Strategic planning of tourist activity in Panorama Tabek Patah with interpretation 63.07% with range score â‰¥ 61.75. While based on each sub activity indicators of tourist sightseeing with a score of 13.38, hiking with a score of 16.25 and flying fox by a score of 16.25 by category strongly agree.Keywords: Strategic Planning, activity outdoors